HLA-A*24:07 as a potential biomarker for carbamazepine-induced Stevens–Johnson syndrome/toxic epidermal necrolysis in Filipino patients - Capule, Francis (Pharmacogenomics, 2021)
AIM: A case-control study was conducted in Filipino patients to determine the association between HLA alleles and carbamazepine-induced Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN). MATERIALS & METHODS: A retrospective review of medical records and data collection were performed. A total of 10 carbamazepine-induced SJS/TEN cases and 40 tolerant controls were recruited. Genomic DNA extracted from saliva samples was genotyped. Statistical analysis was done. RESULTS: The HLA-B75 serotype (p = 0.003; odds ratio [OR] = 13.8; 95% CI = 2.5–76.8), HLA-B*15:21 (p = 0.041; OR = 4.7; 95% CI = 1.1–20.8) and HLA-A*24:07 (p = 0.032; OR = 6; 95% CI = 1.2–30.7) were significantly associated with carbamazepine-induced SJS/TEN. CONCLUSION: The HLA-B75 serotype, HLA-B*15:21 or HLA-A*24:07 may be used for pharmacogenetic screening prior to prescribing carbamazepine in Filipinos.